STRATEGI KEBIJAKAN PEMERINTAH KABUPATEN SUMEDANG DALAM PENYALURAN BANTUAN SOSIAL DI MASA PANDEMI COVID-19 - Nugrahana Fitria Ruhyana; Hadi Ferdiansyah (Khazanah Intelektual, 2020)
The Covid-19 pandemic has caused massive social restrictions so that many people's productive activities have been disrupted, which has led to increased poverty. To overcome this, the government is trying to channel a social safety net for the poor and near-poor. However, the distribution of social safety nets so far has not been fully targeted, thus reducing the effectiveness of these funds. This study aims to provide alternative policies for the Sumedang Regency Government in overcoming the problem of distributing social safety nets to make them more targeted. The method used is a problem solving approach based on literature studies. The fundamental problem with the ineffective social safety net is the inaccurate data on beneficiaries. It requires active community participation in data collection on the poor who deserve to receive a social safety net. Another policy that can be taken so that the beneficiaries do not increase is by providing a psychological effect in the form of labeling the social safety net recipient's house.